Retrograde Carotid Stenting Using Newly Released Venous Stent for Cerebral Malperfusion in Type A Aortic Dissection. (June 2022) - Mukherjee, Dipankar; Lewis, Elizabeth; Spinosa, David; Tang, Daniel; Ryan, Liam
Stanford Type A aortic dissections (TAAD) should be considered for repair, given the involvement of branch vessels which can result in malperfusion, specifically cerebral malperfusion secondary to dissection of the innominate and carotid arteries. This is a case report with a focus on four patients presenting with both acute and chronic symptomatic TAAD, with extension into the innominate and common carotid arteries. In all four cases, the decision to intervene utilizing a hybrid endovascular approach was made to increase perfusion to the brain and alleviate symptoms. Through the use of retrograde carotid stenting utilizing both the VICI venous stent (Boston Scientific, Marlborough, MA) and Abre self-expanding Nitinol stent (Medtronic, Minneapolis, MN) we obtained good results, specifically absence of symptoms and return to normal function of the patients.